Cannabinoid 2 receptor attenuates inflammation during skin wound healing by inhibiting M1 macrophages rather than activating M2 macrophages - Yu Du; Peng Ren; Qi Wang; Shu-Kun Jiang; Miao Zhang; Jiao-Yong Li; Lin-Lin Wang; Da-Wei Guan (BMC, 2018)
Abstract Background The anti-inflammatory properties of the cannabinoid 2 receptor (CB2R) in injury and inflammatory diseases have been widely substantiated. Specifically, the anti-inflammatory effect of CB2R may be achieved by regulating macrophage polarisation. Several research findings suggested that the activation of CB2R could attenuate inflammation by reducing pro-inflammatory M1 macrophage polarisation and promoting anti-inflammatory M2 polarisation. However, considering CB2R inhibits fibrosis and M2 promotes fibrosis, that the activation of CB2R may lead to an increase in M2 macrophages seems contradictory. Therefore, we hypothesised that the activation of CB2R to attenuate inflammation is not achieved by up-regulating M2 macrophages. Methods We established an incised wound model using mouse skin and used this to evaluate the effect of CB2R agonists (JWH133 or GP1a) and an antagonist (AM630) on wound healing. At various post-injury intervals, we used western blot analysis, immunofluorescence staining, enzyme-linked immunosorbent assay and quantitative reverse transcription polymerase chain reaction assays to determine CB2R protein expression, M1/M2 macrophage infiltration, and the protein and gene expression of M1/M2-associated markers and cytokines in skin lesions. Results Activation of CB2R significantly reduced M1 macrophage infiltration and slightly increased M2 macrophage infiltration. Similarly, gene expression and protein levels of M1-associated markers and cytokines (interleukin [IL]-6, IL-12, CD86 and inducible nitric oxide synthase) were significantly down-regulated after CB2R agonist administration; in contrast, markers and cytokines were increased in the CB2R antagonist-treated group. Conversely, the administration of agonists slightly increased gene expression and protein levels of M2-associated markers and cytokines (IL-4, IL-10, CD206 and arginase-1 [Arg-1]); however, a statistical significance at most time points post-injury was not noted. Conclusion In summary, our findings suggested that during incised skin wound healing in mice, increased levels of CB2R may affect inflammation by regulating M1 rather than M2 macrophage subtype polarisation. These results offer a novel understanding of the molecular mechanisms involved in the inhibition of inflammation by CBR2 that may lead to new treatments for cutaneous inflammation.